Exploring qualities of ethnically diverse parents related to the healthy home environment of toddlers. (1st December 2021) - Cepni, Aliye B.; Taylor, Ashley; Thompson, Debbe; Moran, Nancy E.; Olvera, Norma; O'Connor, Daniel P.; Johnston, Craig A.; Ledoux, Tracey A.
Abstract: Parents serve as role models and household policy makers for their children's home social environment. Also, parents may influence the home physical environment through the provision of resources to support their children's dietary, activity, and sleep behaviors. Understanding the parental characteristics related to children's home environment may allow for tailoring obesity interventions to families' needs. This study aimed to explore parental qualities (general parenting styles, parent feeding practices, and parental BMI) related to healthy home food, physical activity, media and sleep environment of toddlers. A total of 50 multi-ethnic parents with toddler age children who were enrolled in a randomized pilot study of a wellness program completed the Structure and Control in Parent Feeding (SCPF) questionnaire and Comprehensive General Parenting Questionnaire (CGPQ). Parental BMI was calculated using self-reported weight and height data. The Healthy Home Survey, the Home Food Inventory, the Sleep Environment Questionnaire, and items developed for this study were standardized and summed to create home food, physical activity, screen media, and sleep environment scores; high scores reflected healthier environments. To examine the relationships between parental qualities and the home environment, Pearson's correlation test was performed. Parental BMI and overall healthy home environment were inversely associated (r = -0.306; p = 0.032) . Structure in general parenting and parental feeding practice were positively correlated with the overall healthy home environment (r = 0.336; p = 0.026) and healthy home food environment (r = 0.415; p = 0.003), respectively. The coercive control general parenting was inversely related to overall healthy home environment score (r = -0.333; p = 0.022) . Based on the findings from this study, parents who provide clear communication, set consistent rules, avoid pressure to control their child's behavior, and have lower BMI tend to live in a home environment that support children's health behaviors.